Using counterfactual thinking theory to change alcohol protective behavioural strategy use intentions. Issue 1 (2nd June 2021) - De Leon, Ardhys N.; Dvorak, Robert D.; Smallman, Rachel; Arthur, Kianna; Piercey, Cianna
Abstract : Objectives: Despite numerous drinking interventions, alcohol use among college students remains a significant problem. Typically activated after negative events, counterfactual thinking is a cognitive process that contrasts reality with an imagined better alternative. As a result, counterfactual thinking highlights potential causal links between problematic behaviours and negative outcomes, which can strengthen intentions to change behaviour. Recent research has found that modifying behavioural intentions to engage in protective behavioural strategies (PBS) has led to increased PBS use and reduced alcohol outcomes. The current study evaluated counterfactual thinking as a way to increase PBS use intentions. Design: Intervention US study with college student drinkers. Methods: A sample of college students ( n = 466) completed a web‐based assessment of demographics, drinking, alcohol consequences, and PBS use. Those who endorsed an adverse drinking event were randomly assigned to an intervention condition (Control, Negative event only, Negative event with description, or Negative event with counterfactual). Following the intervention, participants reported intentions to engage in each PBS subtype over the next week. Results: Relative to control, the counterfactual condition resulted in greater PBS use intentions across all subtypes. Neither the negative event only nor the negative event with description resulted in higher PBS use intentions, relative to control. Importantly, the control group did not report whether they experienced a negative event; thus, we cannot definitively determine the effect this may have on the data. Conclusions: This study provides a new theory‐driven avenue for alcohol use interventions utilizing counterfactual thinking to enhance safe drinking intentions.